MEMRI is a biomarker defining nicotine-specific neuronal responses in subregions of the rodent brain - Bade, Aditya N (Am J Transl Res, 2017)
Nicotine dependence is defined by dopaminergic neuronal activation within the nucleus accumbens (ACB) and by affected neural projections from nicotine-stimulated neurons. Control of any subsequent neural activities would underpin any smoking cessation strategy. While extensive efforts have been made to study the pathophysiology of nicotine addiction, more limited works were developed to find imaging biomarkers. If such biomarkers are made available, addictive behaviors could be monitored noninvasively. To such ends, we employed manganese (Mn(2+))-enhanced magnetic resonance imaging (MEMRI) to determine whether it could be used to monitor neuronal activities after acute and chronic nicotine exposure in rats. The following were observed. Mn(2+) infusion identified ACB and hippocampal (HIP) neuronal activities following acute nicotine administration. Chronic exposure was achieved by week long subcutaneously implanted nicotine mini-pump. Here nicotine was shown to activate neurons in the ACB, HIP, and the prefrontal and insular cortex. These are all central nervous system reward regions linked to drug addiction. In conclusion, MEMRI is demonstrated to be a powerful imaging tool to study brain subregion specific neuronal activities affected by nicotine. Thus, we posit that MEMRI could be used to assess smoking-associated tolerance, withdrawal and as such serve as a pre-clinical screening tool for addiction cessation strategies in humans.